Efektivitas Pembelajaran Menggunakan Aplikasi Canva Sebagai Upaya Meningkatkan Minat Belajar Mata Kuliah Enterpreneur 1 Universitas Bhinneka PGRI (Studi Pada Mahasiswa Prodi Pendidikan Ekonomi Semester VIII Tahun Akademik 2024/2025) - Readytama, Eriko Tasda; Suryaningsih, Tutut (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Canva is a visual design application used in learning to increase students interest and participation. This study aims to determine the effectiveness of using Canva in enhancing students’ learning interest in the Entrepreneur 1 course. The research was conducted at Universitas Bhinneka PGRI with subjects being 8th-semester students of the Economics Education program in the 2024/2025 academic year. The research method used was a qualitative approach with data collection techniques including observation, interviews, and documentation. The results of the study indicate that the use of Canva can enhance students’ attention to the material, improve conceptual understanding, and encourage active participation through presentation tasks and business idea visualizations. However, overly crowded designs may distract students’ focus, indicating the need for a balance between content and visuals.